Analisis Implementasi Program Tabungan Haji Pelajar melalui Edukasi Haji sejak Dini di SDN 03 Pakan Kurai - Putri, Khoriyatus Solehah; Mansur, Yuwarman (ARZUSIN, 2026)
The Student Hajj Savings Program is an Islamic banking innovation that functions as a means of fund mobilization as well as a medium for hajj education from an early age. However, the low habit of saving and the limited understanding of students regarding hajj planning indicate that the implementation of this program has not been optimal. This study aimed to analyze the implementation of the Student Hajj Savings Program through hajj education from an early age at SDN 03 Pakan Kurai. This study used a descriptive qualitative approach with the CIPP evaluation model (Context, Input, Process, Product). Data were collected through interviews, observation, and documentation. The results showed that the program had been implemented fairly well and was relevant to students’ needs. In the context aspect, the program was in accordance with the condition of students’ low financial literacy. In the input aspect, the program was supported by a savings product based on a flexible and easily accessible wadiah contract. In the process aspect, the program was implemented routinely but was not yet optimal due to limited socialization and continuous assistance. In the product aspect, the program had a positive impact on increasing awareness of saving and basic understanding of hajj, although fund accumulation was not yet maximized. The conclusion of this study emphasizes that the success of the Student Hajj Savings Program is determined not only by product design but also by synergy among the bank, school, and parents. The implications of this study indicate the importance of strengthening continuous education and increasing parental involvement to optimize the program as a medium for Islamic financial literacy and character education from an early age.